THE INFLUENCE OF TRANSFORMATIONAL LEADERSHIP, ORGANIZATIONAL COMMITMENT, AND JOB SATISFACTION ON ORGANIZATIONAL CITIZENSHIP BEHAVIOR (OCB) (STUDY AT ST CAROLUS HOSPITAL JAKARTA) - Rama Kelana, Robertus; Tajuddin Pogo (Dinasti Publisher, 2022)
The research which was written with